Organoleptic Characteristics of Mixed Corn Flour And Red Bean Flour Against Crackers - Khoiriyah U Jamlean; Syane Palijama; Gilian Tetelepta (Jurnal Agrosilvopasture-Tech, 2022)
Crackers are crispy, thin biscuits or wafers made from wheat flour. Today, crackers can be innovated with local food commodities such as corn and red beans. The use of the formulation of corn flour to red bean flour can affect the organoleptic properties of crackers. This study aimed to test the appropriate formulation of corn flour and red bean flour for making crackers. This study used 4 formulations of corn flour to red bean flour of 80%: 20%, 70%: 30%, 60%: 40%, and 50%: 50%. The results showed that the formulations of 60% corn flour and 40% red bean flour was the best formulation that produced crackers with liked for their color (3.24), somewhat liked for their taste (2.48), rather liked for their texture (1.52), liked for their aroma (3.16), and also for their overall preferences (2.52). The crackers were perceived to have a yellow color (3.08), a corn flavor (2.76), a savory taste (2.68), and a slightly crunchy texture (1.84).